Analisis Yuridis Terhadap Implementasi Undang-Undang Penghapusan Kekerasan Dalam Rumah Tangga bagi Perempuan Korban KDRT di Indonesia - Yusdhistira, Dhimas Ragil; Suherman, Asep (CV WAHANA PUBLIKASI, 2022)
Domestic violence (KDRT) as a type of gender-based violence continues to increase over time. Juridically, awareness of all parties, both national and international, has been realized, where the enactment of Law Number 23 of 2004 shows the government's concern for women, especially the elimination of domestic violence. In fact, with the publication of this Law, there was a shift from private law issues to public law. This means that in increasing women's protection, the state intervenes in determining punishments for perpetrators of violence. The benchmark for success in Law no. 23 of 2004 concerning the Elimination of Domestic Violence can be seen from the level of domestic violence cases that occur in Indonesia, in fact in 2023, based on the records of the National Commission on Women, it is known that the number of violence against women in 2023 will be 289,111 cases. This number is a relatively large number considering that it was calculated only in the last year. The research results show the effectiveness of Law no. 23 of 2004 in preventing domestic violence is not optimal due to several things, namely the focus of Law no. 23 of 2004, which still focuses on law enforcement, is not yet optimal, many domestic violence victims are reluctant to report when they experience domestic violence, and law enforcement officials do not yet have a completely uniform perspective in handling domestic violence cases.